2014
DOI: 10.1111/bdi.12203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ANK3 and CACNA1C variants identified in bipolar disorder whole genome sequence data

Abstract: ObjectivesGenetic markers in the genes encoding ankyrin 3 (ANK3) and the α-calcium channel subunit (CACNA1C) are associated with bipolar disorder (BP). The associated variants in the CACNA1C gene are mainly within intron 3 of the gene. ANK3 BP-associated variants are in two distinct clusters at the ends of the gene, indicating disease allele heterogeneity.MethodsIn order to screen both coding and non-coding regions to identify potential aetiological variants, we used whole-genome sequencing in 99 BP cases. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 71 publications
(90 reference statements)
2
46
0
Order By: Relevance
“…Although carefully screened, the control group was selected from the general population, thus some subjects may have a disposition for BPD not yet revealed. Of note, investigations on 3 of the SNPs analyzed, rs1016388 [56], rs2337980 [44], and rs6494223 [12,45], respectively, were previously reported on larger GWAS analyses. The cited GWAS reported no significant associations on the sample analyzed; thus, the data we obtained should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Although carefully screened, the control group was selected from the general population, thus some subjects may have a disposition for BPD not yet revealed. Of note, investigations on 3 of the SNPs analyzed, rs1016388 [56], rs2337980 [44], and rs6494223 [12,45], respectively, were previously reported on larger GWAS analyses. The cited GWAS reported no significant associations on the sample analyzed; thus, the data we obtained should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that one or a few rare variants of large effect dramatically increase disease risk, resulting in an inheritance model resembling monogenic inheritance in a given family. However, four exomesequencing and whole-genome sequencing (WGS) studies of BD pedigrees have detected few, if any, plausible variants of large effect (6)(7)(8)(9). An alternative oligogenic model posits that different combinations of several uncommon or rare variants of moderate effect cluster in affected individuals and collectively cause disease.…”
mentioning
confidence: 99%
“…Based on the phenotypic observations of BD, in which there is full recovery between two states, it was suggested that the etiological base-pair changes could be affecting gene expression and mRNA translation rather than causing structural changes in proteins. Potential novel variants identified further need replication and validation in independent samples (27).…”
Section: Whole Genome Sequencingmentioning
confidence: 99%